R. del Valle Inclán’s Novel Tirano Banderas in the Light of Intersectional Analysis - Natalia Iu. Kharitonova (Studia Litterarum)
Spanish writer R. del Valle Inclán wrote the novel Tirano Banderas (1926), when Spain was developing a new policy towards the Latin America after the definite loss of its overseas colonies in 1898. Valle Inclán advocated the restoration of indigenous peoples’ rights, political and economic sovereignty of the Latin American countries. The intersectional analysis clarifies the writer’s anticolonial concept. On the basis of racial identity, the novel’s characters form two groups: Spaniards and foreigners, and Indians and Creoles. Indians are an oppressed race, while the Spaniards and foreigners are oppressors. But General Santos Banderas, who tyrannizes his country, is an Indian too. Additional light is shed due to the analysis of gender and social role and its symbolic dimensions. The female characters in the novel forced to ask men for help but their demands are justified if they act in the interests of their children. Paternity also has the connotations of care and protection, and symbolically, care for the nation. The tyrant Banderas, who kills his insane daughter, fails both as father and as an Indian ruler since he appropriates the oppressor’s role imported from the metropolis.